Characteristics of the high temperature mechanisms of creep and recovery in graphite - College of Aeronautics, (Cranfield) (College of Aeronautics, 1962)
The report summarizes the first year's work carried out on an investigation into the high temperature mechanisms of creep and recovery in graphite. This work has been devoted to the building of an experimental apparatus capable of exerting creep loads in the temperature range 2000°C — 3000°C. A full description of the apparatus is given and its further potential discussed. Detailed figures are included on the labour expended together with a summary of property acquired for use on the contract.